1986
DOI: 10.1109/tps.1986.4316615
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Plasma Universe: I. Double Radio Galaxies, Quasars, and Extragalactic Jets

Abstract: Abstract-Cosmic plasma physics and our concept of the universe is in a state of rapid revision. This change started with in-situ measurements of plasmas in Earth's ionosphere, cometary atmospheres, and planetary magnetospheres; the translation of knowledge from laboratory experiments to astrophysical phenomena; discoveries of helical and filamentary plasma structures in the Galaxy and double radio sources; and the particle simulation of plasmas not accessible to in-situ measurement. Because of these, Birkeland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 89 publications
0
13
0
Order By: Relevance
“…This viewpoint was presented by Trubnikov (1 990). The arguments pointing out at the presence of the currents up to 1019 A in the galactic environment were presented by Peratt (1986Peratt ( , 1990. cm (Yusef-Zadeh et al, 1984).…”
Section: The Stagnation Phasementioning
confidence: 99%
“…This viewpoint was presented by Trubnikov (1 990). The arguments pointing out at the presence of the currents up to 1019 A in the galactic environment were presented by Peratt (1986Peratt ( , 1990. cm (Yusef-Zadeh et al, 1984).…”
Section: The Stagnation Phasementioning
confidence: 99%
“…As charged particles tend to flow in force-free directions, currents tend to be magnetic field-aligned in which case they are often called "Birkeland" currents after Professor Birkeland who first suggested such currents flow in the Earth's magnetosphere (Egeland and Leer, 1986). Their existence is now firmly established and it has been found that they are intimately connected to "inverted V" events, the generation of aurora, and the generation of electromagnetic radiation in the range from a few Hertz to many megahertz It is also thought that Birkeland currents are of importance throughout the Universe on a variety of scales up to galactic scales (Faelthammar, 1986;Peratt, 1986Peratt, ,1988Peratt, ,1990. It is therefore not surprising that the scientific community has shown considerable interest in performing space experiments which involve the ejection of electron beams and the formation of artificially generated currents.…”
Section: Introduci'ionmentioning
confidence: 99%
“…INTRODUCTION T HE evolution of cosmic plasma from a filamentary state to the development of double radio sources and quasars was investigated in the first part to this sequel paper (Paper I) [1]. The time frame of this study, based upon scaling simulation parameters to galactic dimensions, spanned some 108_109 years.…”
mentioning
confidence: 99%
“…The basic model of the plasma universe, inspired by the observation that most cosmic plasmas are filamentary in structure [6], consists of studying the interaction between current-conducting galactic-dimensioned plasma filaments aligned along magnetic field lines (Birkeland currents, [1]). Although the entire filamental circuit is expected to be hundreds of megaparsecs in length and is probably no less complex than the magnetospheric current distribution near Earth, only a fraction of the circuit is simulated.…”
mentioning
confidence: 99%
See 1 more Smart Citation